Detection by Direct Next Generation Sequencing Analysis of Emerging Enterovirus D68 and C109 Strains in an Environmental Sample From Scotland - Majumdar, Manasi; Martin, Javier (Frontiers in Microbiology, 2018)
Background: Human enteroviruses (EVs) have been linked with severe disease and syndromes as varied as acute respiratory illness, myocarditis and flaccid paralysis. With global polio eradication on sight the focus of clinical investigations has expanded to the identification of other EV serotypes associated with severe neurological conditions such as EV-D68, responsible for large outbreaks in 2014 and 2016 that spread worldwide and were related with severe respiratory disease leading to acute myelitis in some cases. New EV serotypes with epidemic potential continue to emerge such as EV-C104, EV-C105, EV-C109 and EV-C117 identified in respiratory samples in recent years. Methods: We used a next generation sequencing (NGS) approach to detect multiple EV serotypes directly in a sewage concentrate from Glasgow (Scotland, UK) generating whole-capsid nucleotide sequences that were compared to sequences of cell culture isolates from this sewage sample and clinical EV isolates from GenBank. Results: Thirteen different serotypes belonging to all four A, B, C and D EV species were identified in the sewage concentrate. EV strains closely related to EV-D68 epidemic isolates of B3 lineage reported in the USA and Europe in 2016 and to EV-C109 respiratory isolates found in Denmark and the Netherlands in 2015 were identified. Conclusions: Environmental surveillance (ES) can effectively detect EV circulation in human populations. The use of NGS for ES can help overcoming the limitations of traditional cell culture and sequencing methods, which are selective and biased, and can contribute to the early detection and assessment of spread of emerging EV pathogens.